Hindfoot arthroscopy management of flexor hallucis longus tenosynovitis: 24-month outcomes
Objective: We present a series of patients with flexor hallucis longus tenosynovitis submitted to hindfoot endoscopy, describing clinical outcomes and reporting surgical findings and complications seen throughout the treatment. Methods: Thirty-one patients diagnosed with flexor hallucis longus tenosynovitis submitted to posterior ankle endoscopy were followed. The mean follow-up was 24 months. Patients were classified according to American Orthopaedic Foot and Ankle Society (AOFAS) and Visual Analogue Scale (VAS) scores. Patient satisfaction was measured. Results: The mean age of patients was 35.13 (Å